Femonationalism and anti-gender backlash: the instrumental use of gender equality in the nationalist discourse of the Fratelli d'Italia party - Colella, Daria (Gender and development, 2021)
In the context of the current escalation of anti-gender backlash, this article analyses the instrumental use of gender equality by nationalist forces and unpacks the ways in which the latter dynamic threatens feminist politics and gender justice. I study the intersection of gender and sexuality issues with the co-option of selected aspects of the feminist project by right-wing parties and I reflect on the ways in which femonationalist actors enable and fuel the attacks on women and LGBTQI+ people. In particular, I investigate the instrumental use of gender equality to vilify Black and People of Colour migrants and promote anti-immigration sentiments, with a focus on the framing of gender-based violence in racialised terms. By applying a postcolonial lens, I analyse the redeployment of the gendered colonial narrative in the context of contemporary metropolis focusing on the discourse of the far-right Italian party Fratelli d'Italia. I demonstrate that femonationalist discourses (1) reinforce gendered and racialised power structures, hence patriarchal and heteronormative values; and (2) reshape the understanding of gender equality issues, diluting the meaning of activists' demands. Unpacking the convergence between femonationalism and anti-gender backlash, the paper provides insights on the complexity of the latter phenomenon and contributes to an understanding of the necessity of challenging the narratives promoted by nationalist discourses to dismantle unequal power relations and all hierarchies of dominations. I conclude by discussing the need for feminists to form intersectional alliances among the oppressed to remain true to their emancipatory and transformative political project and build sustainable, equitable, and inclusive movements.